ANALISA KRITIS TERHADAP PENENTUAN MASA DALUARSA DALAM TINDAK PIDANA PEMALSUAN SURAT - Aris Sardister Gultom; Rasji Rasji (PROSIDING SERINA, 2021)
Indonesia is a state based on law. In the conception of the rule of law, it is determined that every action of a state administrator must be based on applicable law. The legal system that applies in Indonesia is the Continental European legal system (civil law system) with the main characteristic that the law will only have binding power if it is materialized in the form of statutory regulations. Where the main emphasis on this legal principle is legal certainty. Legal certainty extends beyond the limited interpretation to the material of legislation contained within itself, but legal certainty must be interpreted as a legal guarantee for justice and norms of kindness to the people. Therefore, it is important that there is harmony between the material contained in the legislation and the legal ideals stipulated in the Indonesian state. So that the law is authoritative, just and beneficial for the people of Indonesia. In practice, the existing laws and regulations have yet to provide legal certainty, justice or benefits for the justice seekers community (Justiciabelen), for example, the provisions contained in Article 78 paragraph (3) of the Criminal Code regarding expiration are determined; "Regarding crimes punishable by imprisonment for more than three years after twelve years" with the calculation of the grace period starting to come into force determined based on Article 79 of the Criminal Code, namely; "on the day after the deed is done". As a result. the limitation on the calculation of expiration specified in Article 79 of the Criminal Code has amputated the private rights of the community in protecting their family or individual honor as victims of the crime of forging letters whose criminal events are only known decades later and beyond the expiration period specified in the Criminal Code.Negara Indonesia merupakan Negara hukum. Pada konsepsi negara berdasarkan hukum tersebut ditentukan tiap tindakan penyelenggara negara mesti didasarkan pada ketentuan hukum yang berlaku. Adapun sistem hukum yang berlaku di Indonesia adalah sistem hukum Eropa Kontinental (civil law system) dengan karakteristik utamanya hukum hanya akan memiliki daya ikat apabila diwujudkan dalam bentuk peraturan perundang–undangan. Dimana penekanan utama pada prinsip hukum ini adalah kepastian hukum. Kepastian hukum tidak cukup dimaknai sebatas pada materi Perundang-undangan dimuat pada Perundang-undangan itu sendiri akan tetapi kepastian hukum haruslah dimaknai sebagai suatu jaminan hukum terhadap keadilan dan norma-norma kebaikan terhadap rakyat. Oleh sebab itu penting adanya keselarasan antara materi dimuat dalam Perundang-undangan terhadap cita hukum ditetapkan dalam negara Indonesia. Sehingga hukum itu berwibawa, berkeadilan dan bermanfaat bagi rakyat IndonesiaPada praktiknya justru Peraturan Perundang-undangan yang ada dirasa tidak memberikan kepastian hukum, keadilan atau kemanfaatan bagi masyarakat para pencari keadilan (Justiciabelen), sebut saja diantaranya ketentuan dimuat pada pasal 78 ayat (3) KUHP terkait kedaluarsa ditentukan; “Mengenai kejahatan yang diancam dengan pidana penjara lebih dari tiga tahun sesudah dua belas tahun” dengan perhitungan tenggang waktu mulai berlakunya ditentukan berdasarkan Pasal 79 KUHP, yaitu; “pada hari sesudah perbuatan dilakukan”. Akibat dari pembatasan perhitungan kedaluarsa ditentukan pada Pasal 79 KUHP telah mengamputasi hak-hak pribadi masyarakat dalam melindungi kehormtan keluarga atau pribadinya selaku korban dari tindak pidana pemalsuan surat yang peristiwa pidananya baru diketahui setelah puluhan tahun kemudian dan melampaui masa kedaluarsa ditentukan dalam KUHP.